ANALISIS KEPATUTAN DUE DILIGENCE YANG DIKEMBANGKAN LEMBAGA MODAL VENTURA DALAM HUBUNGANNYA DENGAN AKURASI PENGAMBILAN KEPUTUSAN PEMBIAYAAN (Study Kasus pada Perusahaan Pasangan Usaha dari PT. Sarana Jakarta Ventura) - Kartono Kartono (Universitas Pamulang, 2015)
The purpose of this study, to determine the technical due diligence undertaken in order to finance the preparation of feasibility study, as well as determine the extent to which the implementation of the due diligence carried out as a basis for determining the propriety of a business feasibility study financing in PT Sarana Jakarta Ventura so that it can be evaluated. The study was conducted by using descriptive analysis method. The analysis tool used is the analysis of qualitative data, which can be drawn a conclusion on the discussion that has been carried out as follows: (1) PT.Sarana Jakarta Ventura using techniques due diligence generally refers to the analysis of the feasibility of the work done by financial institutions and Banks , (2) The process of due diligence carried out by analyzing the important aspects related to the financing plan (technical aspects of production and operations, legal aspects and legal, organizational aspects and management, financial aspects), there are still weaknesses that some of the potential risks of financing undetected, because in the process of verification, evaluation, assessment and analysis of aspects of financing that do not sharp and accurate, even there are important aspects of the financing just does not do the analysis, namely the management aspects related to the analysis of 5C with prudential principles. The results of this study suggested that companies should create guidelines for financing that can be used to perform due diligence in relation to the accuracy of decision making financing set forth in the Product Program Manual Investments (PPM Investments) and required the understanding and commitment of the parties involved in the decision process financing.Keywords: Business Feasibility Studies, Due Diligence, Venture Capital Company